2023
DOI: 10.21511/ppm.21(2).2023.45
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in entrepreneurial interest and practice among undergraduate students in Nigeria

Abstract: The economic turbulence in the last two decades and the Covid-19 pandemic have impaired several economies, heightened unemployment, and worsened job loss and socio-economic hardships. Promoting entrepreneurship inclusiveness has become a critical strategy to revamp the economy. Meanwhile, the global economy has been projected to grow faster with an increase in women entrepreneurs. However, there seems to be a gender gap and differential in start-ups, which draws down women’s inclusion in the business environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…These results are essential considering the psychological nature of the male and female populations, which could have differences in their perceptions (Hyde, 2014). Recent studies reported that male university students showed higher entrepreneurial self-efficacy than women in the business environment (Adelowo and Akinwale, 2023). This result is consistent with the North American study where female students showed lower self-efficacy and entrepreneurial intention scores than males (Neumeyer, 2022).…”
Section: Discussionsupporting
confidence: 78%
“…These results are essential considering the psychological nature of the male and female populations, which could have differences in their perceptions (Hyde, 2014). Recent studies reported that male university students showed higher entrepreneurial self-efficacy than women in the business environment (Adelowo and Akinwale, 2023). This result is consistent with the North American study where female students showed lower self-efficacy and entrepreneurial intention scores than males (Neumeyer, 2022).…”
Section: Discussionsupporting
confidence: 78%